The effect of aerobic and anaerobic exercises on stress and secretion of cortisol in young male soccer players - Biçer, Süreya Yonca; Asghari, Akbar; Imanzadeh, Masoud; Asl, Nader Shaygan (My University, 2011)
The objective of this research was to study the effect of aerobic and anaerobic exercises on stress and secretion of cortisol in young male soccer players. Cortisol is a stress hormone which is secreted in reaction to stress and highly affects carbohydrate, fat, and protein metabolisms and has a stimulating effect on central nervous system and circulatory system. In this research which was semi-empirical, of 250 soccer players with the average age of 16 to 19 years, 20 were chosen and divided into two groups of 10 subjects; an aerobic exercise group that performed a 2400-meter run test and ananaerobic exercise group that performed sprints (100, 200 and 400 meters). Hari's Stress Inventory was used for those players with high level of stress. In order to determine the concentration of cortisol, blood sampleswerecollected from each group before and after aerobic and anaerobic exercises. Results were assessedat significance level of p<0.05 and using t-test for dependent samples. The results showed that bothan aerobic exercise session and an anaerobic exercise session significantlyaffect blood concentration and cortisol secretion and that these exercise sessions have no significant effect on the reduction of stress.
Keywords: Aerobic and anaerobic exercise; Cortisol; Soccer players; Stress